2009
DOI: 10.1002/mrm.22005
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of cerebral blood flow, cerebral blood volume, and blood–brain‐barrier leakage with DCE‐MRI

Abstract: Dynamic susceptibility contrast MRI (DSC-MRI) is the current standard for the measurement of Cerebral Blood Flow (CBF) and Cerebral Blood Volume (CBV), but it is not suitable for the measurement of Extraction Flow (EF) and may not allow for absolute quantification. The objective of this study was to develop and evaluate a methodology to measure CBF, CBV, and EF from T1-weighted dynamic contrast-enhanced MRI (DCE-MRI). A twocompartment modeling approach was developed, which applies both to tissues with an intac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
251
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(262 citation statements)
references
References 46 publications
7
251
2
1
Order By: Relevance
“…31,32 Many previous studies have reported significantly decreased ADC and R 2 in cases of overt BBB disruption, suggesting that these parameters may be correlative indices for describing strokeinduced BBB damage. [13][14][15][16][17] On the contrary, in the current study, we observed similar infarct ADC and R 2 values that were independent of the WEI. The discrepancy principally results from different scales of BBB injury between studies.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…31,32 Many previous studies have reported significantly decreased ADC and R 2 in cases of overt BBB disruption, suggesting that these parameters may be correlative indices for describing strokeinduced BBB damage. [13][14][15][16][17] On the contrary, in the current study, we observed similar infarct ADC and R 2 values that were independent of the WEI. The discrepancy principally results from different scales of BBB injury between studies.…”
Section: Discussioncontrasting
confidence: 70%
“…According to previous study results, alterations in CBV, ADC, and R 2 were positively predictive of BBB disruption, as all of these parameters significantly decreased in ischemic stroke characterized by extravasation of contrast materials. [13][14][15][16][17] However, under such heavy ischemic stresses that lead to overt vascular disruption, changes in these MRI parameters may be derived not only from the weakened BBB itself, but also from other ischemia-affected tissue/vascular conditions including cytotoxicity, inflammation, and edema formation. 3,18,19 Therefore, overly simplified dichotomous division of stroke cases according to the presence of apparent trans-BBB leakage does not definitively identify the causative factors in the BBB disruption.…”
Section: Introductionmentioning
confidence: 99%
“…This is desirable, i.e., when studying brain barrier leakage [51], tumors [52], or kidney filtration [4,11,18]. Such tasks can be performed when applying compartment models [6,19].…”
Section: Discussionmentioning
confidence: 99%
“…8,9,15 For that reason, some authors have proposed performing 2 injections of 0.05 mmol/kg of gadolinium for DCE MR imaging to minimize the error arising from the conversion of signal intensity to gadolinium concentration from magnitude images. 16 While saturation of signal intensity could lead to an underestimation of the contrast agent concentration, the presence of inflow effects could lead to an overestimation. 17 Our magnitude-VIF based K trans and V p estimates were higher than those derived from the phase method.…”
Section: Discussionmentioning
confidence: 99%